Mechanical characteristics of tabletted binary and tertiary pharmaceutical excipient mixtures - Al-Ibraheemi, Zahraa Abdulhussein Mousa (2014)
Various excipients are used in the pharmaceutical tablet industries to present desirable properties in the final product. All excipients should have suitable flowability to produce homogenous distribution at the point of mixing. In addition, the excipients have to be hydrophilic as a disintegrant, have proper compactibility as a binder, and confer acceptable taste results as a diluent. In fact, there is no one type of excipient that has all these characteristics. Therefore, the focus point of this research is to formulate the desirable tablets consisting of different types of excipient mixtures to achieve tablets that meet requirements of recommended tablet formulation. In this study, the components of compacted tablets by direct compression consist of Microcrystalline Cellulose as a plastic material (binder), Sodium Starch Glycolate as an elastic material (super disintegrant), and alpha Lactose monohydrate as a brittle material (filler). The physical and flow properties of the excipients used have been investigated. The uniaxial compaction process was conducted by using a universal testing instrument. The tablets were compacted under pressure ranging from 75 to 375 MPa. A 13 mm diameter cylindrical die was used to investigate the compression characteristics of the single binary and tertiary mixtures with 1.0 ± 0.01 g of powder. The loading and unloading stages of the compaction process for the tablets were evaluated based upon the energies derived from the force-displacement data obtained for the tablets with different mass ratios compacted at 150 MPa. The effect of increasing the compression pressure from 75 to 375 MPa on the volume-pressure measurements for single, binary with different mass ratios and tertiary tabletted mixtures was investigated. The tabletted mixture characteristics and recommended tablet formulations were evaluated by using elastic relaxation, indirect tensile strength, friability, and disintegration tests. The strong influence of the physical powder characteristics on the flow properties of the powders used was observed. The plastic material (MCC) shows a dominant property over the elastic (SSG) and brittle (LAC) materials in terms of their tensile strength and their behaviour during compaction events. Applying a high pressure produces tablets with a low elastic relaxation, higher tensile strength, low friability percentage and a long disintegration time. Increasing the MCC and decreasing LAC and SSG percentages lead to an increase in tensile strength, disintegration time, and decreases the friability percentage. According to the recommended formulation of the tablets, tertiary formulation can be considered as the best formulation. One of the more significant findings to emerge from this study is that the use of mixtures of the direct compression excipients has proven to be significantly more appropriate for use compared to the individual components.